The Use of Marijuana for Medical Purposes: Between Normativity and the Principle of Islamic Law perspective - Achmad Arif; Andini Rachmawati; Imam Kamaluddin; Nurjihan Naifah (Mazahib, 2022)
The limited availability of drugs for rare diseases makes some people use various ways to get treatment. One of them is using marijuana as medicine. In Islam, marijuana is not written directly in the texts, but it can be studied with Islamic legal principles in determining its ruling. Therefore, this paper aims to review the use of marijuana for medical needs from the point of view of the principle of Islamic law “al-ḥukmu yadûru ma’a al-'illah wujûdan wa’ adaman” (the law revolving around the cause for issuing it, whether it is present or absent). This study is library research sourced from the Islamic Jurisprudence references, then analyzed by the inductive method. The research results indicate that marijuana as a treatment is relatively new, and Islamic jurisprudence does not explicitly explain its legal use. Moreover, its use for health services is prohibited in the Narcotics Law. Marijuana in Islam is known to have an intoxicating cause that makes it haram (prohibited). The principle of Islamic law, “al-ḥukmu yadûru ma’a al-'illah wujûdan wa’ adaman” (the law revolving around the cause for issuing it, whether it is present or absent), serves as an excellent guide to know when a law applies and when it is suspended. If there is a cause (‘illah), then there is a law; if there is no cause (‘illah), there is no law. However, the reason (‘illah) with marijuana is a type of common cause (al-'illah al-muta’addiyah) where the branches of law (far’u al-ḥukm) follow the original law. Therefore, the use of medical marijuana is still illegal. Islam allows treatment with forbidden materials (haram) only in emergencies following the terms and conditions of emergency (dharuriyat) in Islam. Keywords: Marijuana, Medical, the principle of Islamic law “al-ḥukmu yadūru ma’a al-'illah wujūdan wa’ adaman” (the law revolving around the cause for issuing it, whether it is present or absent)